Automated Sequential Derivatization for Gas Chromatography-[Orbitrap] Mass Spectrometry-based Metabolite Profiling of Human Blood-based Samples - Akrem Jbebli; Kateřina Coufalíková; Moira Zanaboni; Manuela Bergna; Renzo Picenoni; Jana Klánová; Elliott Price (Bio-Protocol)
Many small molecules require derivatization to increase their volatility and to be amenable to gas chromatographic (GC) separation. Derivatization is usually time-consuming, and typical batch-wise procedures increase sample variability. Sequential automation of derivatization via robotic liquid handling enables the overlapping of sample preparation and analysis, maximizing time efficiency and minimizing variability. Herein, a protocol for the fully automated, two-stage derivatization of human blood–based samples in line with GC–[Orbitrap] mass spectrometry (MS)-based metabolomics is described. The protocol delivers a sample-to-sample runtime of 31 min, being suitable for better throughput routine metabolomic analysis.